A study on sustainable air travel behavior under the possible remedy of risk knowledge: A mediating perspective of risk perception during COVID-19 - Niemtu, Warangsiri; Qin, Kaida; Toseef, Muhammad (Frontiers in Psychology, 2022)
Abstract: The aviation industry is the center of gravity for tourism-dependent countries to uplift economic activities. The COVID-19 pandemic in the early part of 2020 threatened people and the air industry to the maximum extent. This paper investigated the sustainable air-travel behaviour of passengers under the risk knowledge path. The mediating role of risk perception, i.e., physical risk, psychological risk and service quality, is also being tested on the risk knowledge-air travel behaviour association. We surveyed 339 travelers at six airports in Thailand from January to June 2021 to record their responses. We applied structural equation modelling (SEM), and the study results revealed a direct effect of risk knowledge along with an indirect effect via risk perception paths on air-travel behaviour. This paper highlighted knowledge as a remedial answer for the perceptual make-up for the sustainability of air services. The study has strong managerial implications for aviation management to design ideal pathways to retain air services on board during the current public emergency of COVID-19.